Students' Perception on the Use of Grammarly in Writing English Journal - Suci, Intan Putri Permata (JALL (Journal of Applied Linguistics and Literacy), 2024)
Students find writing difficult, particularly when it comes to writing for scientific journals in English. In writing, we must present writing that is interesting, written correctly, systematic, and useful for readers. With technological developments, a tool called Grammarly created to help make writing easier with many uses. The aim of this study is to investigate students perceive the use of Grammarly correcting and revising English written work that takes the style of scientific journals. This research is used a mixed method and the instructions used are questionnaires and interviews. This questionnaire was distributed to 23 postgraduate English language education students at University of Bengkulu and interviews were conducted with 5 representatives to obtain detailed information. The results showed that 79.7% in the Agree category showed that students were helped in using Grammarly in write journals. However, Grammarly has disadvantages, such as not being able to detect the tense used, checking which is not clear, and limited check space for free features. Therefore, in order to use it premium and access a number of additional beneficial features, we must spend a set amount of money.  So, it can be concluded that Grammarly useful and helpful in writing English journals, but is only able to check at a basic level and at more levels does not support proofreading.